MORPHOMETRIC STUDIES ON THE RUMINANT KIDNEYS : BUFFALO, CATTLE AND GOAT - Rahardja, Djoni Prawira; Utomo, T. R.; Sonjaya, H. (Proceeding Buffalo International Conference, 2013)
A morphometric study on ruminant kidney was conducted to elucidate the structural feature of the buffalo, cattle and goat kidneys which attributable with the urinary concentrating capacity. All kidney samples were collected from animals (3-5 years old) slaugthered in Tamangapa Slaugther House, Makassar. The external dimensions of the kidney were measured, including weight, thick, length and wide; the volume were measured according to the Archimedes principle, then used to determine specific density (ds.).Â  The internal dimensions measured were the cortex and medulla thicknesses, which then used to determine some indices : Percentage of Medullary Thickness, Relative Medullary Thickness and Medullary-Cortex ratio.Â  Data were analysed using the procedure of variance analysis based on factorial design of 3 (species) x 2 (sex) x 2 (location) with 5 replications of animal, then significant differences among mean values were determined by the procedures of Duncan Multiple Range Test. The results indicated that the ds and all internal indices were not significantly different between male and female or between left and right kidneys within the same species, while these parameters were significantly different in different species, and the mean value difference were consistent that goats > cattle > buffalo. Accordingly, it can be concluded that the goats with that kidney structural feature have higher concentrating capacity to produce a lower volume with higher osmolality of urine compared to that of cattle and buffalo. Therefore, as an implication is for the small herder, that understanding these characteristics (particularly relating with water availability) may be useful to boost the incomes and to improve the rural farmer livelihood in this region where these three species of ruminants are mostly managed.